LAUNDRY BUSINESS QUALITY CONTROL USING THE DMAIC METHOD (CASE STUDY: DETER_GENT LAUNDRY NUSA DUA BRANCH) - Ni Putu Sugiantari; Ketut Ananda Kuvera Witana, Made Dwitari Utami, Adisty Fayza Wiana, Ni Luh Putu Suciptawati (Adisam Publisher, 2024)
The laundry business is one of the rapidly growing businesses in Indonesia. This development is due to factors such as the increasing busyness of the community, urbanization, and lifestyle changes. Deter_gent Laundry is one of the businesses that experienced a decrease in income and the number of customers from October to November in 2023 due to errors in recording the number of clothes, clothes fading, clothes shrinking, clothes lacking fragrance, and others. This study aims to analyze the problems that occur in the laundry process at Deter_gent Laundry and provide solutions to improve the quality of laundry services. This research uses the DMAIC method (Define, Measure, Analyze, Improve, Control). The results of this study indicate that the problems that occur are caused by several factors, namely human factors, method factors, material factors, and machine factors. To overcome these problems, it can be done by increasing the accuracy of employees, providing explanations, establishing and revising appropriate SOPs, and periodically controlling performance that deviates from SOPs. By implementing these solutions, it is hoped that the quality of laundry services at Deter_gent Laundry can improve and achieve the specified targets.